2018
DOI: 10.17569/tojqi.411971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2017 5th Grade Information Technologies and Software Course Draft Curriculum and 21012 Information Technologies and Software Course Curriculum

Abstract: Advances in information technologies (IT) that became prominent since the 1980's gained significance in the 21st century based on the integration of computer technologies with the education-instruction processes and the developments in the fields of technology. In this context, one of the most important steps taken in Turkey was the introduction of the IT course in almost all educational levels to train qualified computer literate individuals. Various new regulations and developments have introduced to the jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…When reviewing the related literature, it was found that there were studies evaluating the draft form of the 2017 ITS course curriculum (Gündüz & Kuzu Demir, 2018;Information Technology Educators Association, 2017;Karaman & Karaman, 2019;Mercimek & İliç, 2017), yet only one study was found that had www.mojet.net taken the opinions of teachers and students after the implementation of the ITS curriculum in 2017 (Sarıkoz & Bangir Alpan, 2019). This study conducted by Sarıkoz and Bangir Alpan (2019) could not be said to be a curriculum evaluation study because of the purpose and scope of the study as well as the lack of a curriculum evaluation model.…”
Section: Curriculum Evaluationmentioning
confidence: 99%
“…When reviewing the related literature, it was found that there were studies evaluating the draft form of the 2017 ITS course curriculum (Gündüz & Kuzu Demir, 2018;Information Technology Educators Association, 2017;Karaman & Karaman, 2019;Mercimek & İliç, 2017), yet only one study was found that had www.mojet.net taken the opinions of teachers and students after the implementation of the ITS curriculum in 2017 (Sarıkoz & Bangir Alpan, 2019). This study conducted by Sarıkoz and Bangir Alpan (2019) could not be said to be a curriculum evaluation study because of the purpose and scope of the study as well as the lack of a curriculum evaluation model.…”
Section: Curriculum Evaluationmentioning
confidence: 99%
“…It is thought that the scale to be used in the evaluation of the 2017 ITS curriculum in the study will be beneficial in terms of determining the strengths and weaknesses of the curriculum according to the students' views, improving its weaknesses and eliminating the deficiencies of the program. When the literature is examined, it is seen that there are few studies about the evaluation of the 2017 curriculum (Bilişim Teknolojileri Eğitimcileri Derneği [Association of ICT Educators], 2017;Gülbahar & Kalelioğlu, 2018;Gündüz & Kuzu Demir, 2018;Karaman & KAraman, 2019;Mercimek & İlic, 2017). The small number of these studies conducted for the purpose of evaluating the 2017 curriculum is designed with the qualitative research methods using document analysis or teacher opinions as data collection tools.…”
Section: Introductionmentioning
confidence: 99%